THE INFLUENCE OF PERCEIVED VALUE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AND CUSTOMER ENGAGEMENT AS A MEDIATING VARIABLE ON CUSTOMERS PT. JINOM PONOROGO - Ihsan, Abdul Mu’iz Ihsan; Hermawan, Agus; Winarno, Agung (International Journal of Business, Law, and Education, 2023)
The purpose of this analysis is to determine the direct and indirect effects of perceived value on customer loyalty through customer satisfaction and customer engagement on PT JINOM Ponorogo customers. This type of research is descriptive and explanatory research, with a quantitative approach. For data processing using SEM-PLS. Questionnaire survey data was collected using Google Forms. The sample in this study was 208 customers of PT JINOM Ponorogo. The findings show that Perceived value (X) has a positive and significant effect on customer loyalty (Y). Perceived value (X) has a positive and significant effect on customer satisfaction (Z1). Perceived value (X) has a positive and significant effect on customer engagement (Z2). Customer satisfaction (Z1) has a positive and significant effect on customer loyalty (Y). Customer engagement (Z2) has a positive and significant effect on customer loyalty (Y). Customer satisfaction (Z1) has a positive and significant effect on mediating perceived value (X) on customer loyalty (Y). Customer engagement (Z2) has a positive and significant effect on mediating Perceived value (X) on customer loyalty (Y)